Penentuan Kandungan Etanol dalam Makanan dan Minuman Fermentasi Tradisional Menggunakan Metode Kromatografi Gas - dhony hermanto (CHEMPUBLISH JOURNAL, 2020)
Determination of alcohol content in food and beverage is needed for halal verification. Ethanol content in various food and beverage traditional products from fermentation was determined using the gas chromatography method with ethanol as standart and n-buthanol as internal standart. As comparison, measurement using alcohol meter were conducted. The GC measurement result were also compared with alcohol content printed on the packaging (value declared by the producer). The result showed that linear range in ethanol concentration was 1-10% with correlation coefficient (r) of 0.9984, indicated that GC has excellent linearity. Limit of detection was 0,5 ng, coefficient variance (CV) was ≤ 2%, accuracy (K) was ≤ 5% and recovery was > 2%, indicated that GC method has high sensitivity, accuracy, validity and recovery. Alcohol content in beer samples listed in the packaging was confirmed with GC measurement results. Anova test results showed that the GC methods with alcohol meter methods did not differ significantly so that the GC and alcohol meter methods can be used as a good alternative in determining the ethanol content in fermented foods and beverages as a support in halal verification.